Health Law Protection for Students in the Implementation of Free Nutritious Eating Programs based on Presidential Regulation Number 115 of 2025 - Novita Listyaningrum; Sis Nanda Kus Andrianto; Dwi Ratna Kamala Sari Lukman; Awaludin (UNIVERSITAS PAKUAN, 2026)
This study aims to see the health legal protection of the Free Nutritious Eating program, namely preventive legal protection and repressive legal protection. This research uses normative legal research methods with a regulatory approach and a conceptual approach. Preventive legal protection can be seen from the 1945 Constitution providing constitutional legitimacy; The UUPK provides a mechanism for responsibility and compensation; The Food Law guarantees safety and quality standards; The Health Law affirms the right to nutrition and health; and Presidential Regulation 115 of 2025 ensures systematic governance and supervision. Meanwhile, the protection of repressive laws is an important instrument to ensure the restoration of rights and justice for participants who are harmed by non-conformity with nutritional standards. Through a combination of civil, administrative, and criminal accountability mechanisms regulated in the Civil Code, UUPK, Food Law, Health Law, and Presidential Regulation Number 115 of 2025, the state seeks to ensure that the MBG Program is not only administratively operational, but also legally accountable. Keywords: Free Nutritious Eating (MBG), Legal Protection, Preventive Legal Protection, Repressive Legal Protection, Food Safety, Health Law.